Membentuk Karakter Siswa Melalui Nilai-Nilai Kejujuran Terhadap Siswa Kelas IV Era Masa Kini di SDK Marga Bhakti - Darianto; Priyambada, Lazarus Satya; Pius X, Intansakti (Sekolah Tinggi Pastoral IPI Malang, 2023)
Education is also a medium to shape student character so that they become strong personalities and have good character. Education is also a medium to shape student character so that they have a strong personality and have good character. Elementary school is a formal educational institution that aims to develop students to become well-educated and characterized children. research methods based on interpretive philosophy or postpositivism, or used constructively for natural object conditions. and actions, based on religious norms, laws, manners, culture and customs. The mental revolution presents a new mentality that is valuable and noble, which will be revolutionized, namely the mentality of the nation's children who are increasingly chaotic to equip themselves.